Domain of application in context-aware recommender systems: a review - Haruna, Khalid; Ismail, Maizatul Akmar; Mohamed Shuhidan, Shuhaida (2016)
The purpose of this research is to provide an exhaustive overview of the existing literature on the domain of applications in recommender systems with their incorporated contextual information in order to provide insight and future directions to practitioners and researchers.We reviewed published journals and conference proceedings papers from 2010 to 2016.The review finds that multimedia and e-commerce are the most focused domains of applications and that contextual information can be grouped into static, spatial and temporal contexts.